ANN prediction of luminance in road lighting systems - AKAR, ONUR (My University, 2022)
Yol aydınlatması, tüm dünyada olduğu gibi ülkemizde de şehir aydınlatmasının en önemli kısmını oluşturmaktadır. Doğru bir yol aydınlatması, ulaşımda oluşan kaosu çözerken, şehir içi trafik akışının da düzgün olmasını sağlar. Ayrıca iyi yol aydınlatması kişilerin konforlu ve güvenli bir yolculuk geçirmesini sağlar. Akşam saatlerinde kaza sayılarının azaltılabilmesi için sürücülere güvenli sürüş ve görsel konforun sağlanması gerekmektedir. Aşırı aydınlatma, yetersiz yol aydınlatmasının yanı sıra kazalara ve elektrik enerjisinin israfına da neden olmaktadır. Yoldaki nesnelerin iyi görülebilmesi ve sürücülerin görüş rahatlığı için doğru yol aydınlatması, yol yüzeyinde eşit bir parlaklık dağılımı sağlanarak mümkündür. Bu makalede, yol aydınlatmasının parlaklık düzeyinin ölçülmesinde kullanılan yöntemler sistematik olarak araştırılmış ve literatürde olmayan yol aydınlatmasının YSA ile tahminine örnek bir uygulama çalışması yapılmıştır

Road lighting is the most important part of city lighting in our country as well as all over the world. A correct road lighting solves the chaos in transportation and ensures that the traffic flow in the city is smooth. In addition, good road lighting ensures that people have a comfortable and safe journey. In order to reduce the number of accidents in the evening hours, drivers must be provided with safe driving and visual comfort. Excessive lighting causes accidents as well as insufficient road lighting and also causes wastage of electrical energy. Good visibility of objects on the road and correct road lighting for drivers' visibility is possible by providing an even distribution of brightness on the road surface. In this article, different methods used to measure the brightness level of road lighting have been systematically investigated and contributed to the literature from various aspects. In addition, a sample application study has been made about the estimation of road lighting with ANN
Keywords: Yol Aydınlatması; Parıltı; YSA; Road Lighting; Lüminance; ANN